2023
DOI: 10.3390/rs15020441
|View full text |Cite
|
Sign up to set email alerts
|

Inclinometer and Improved SBAS Methods with a Random Forest for Monitoring Landslides and Anchor Degradation in Otoyo Town, Japan

Abstract: Kochi Prefecture is located in an active zone of Japan that is frequently subjected to landslides due to heavy precipitation in typhoon seasons. Slow-moving landslides have been reported by both the local prefectural authorities and the National Government of Japan. We observed landslide movements in Otoyo Town by using ground- and satellite-based tools. Despite the high cost of establishing a borehole inclinometer survey to obtain accurate ground-based measurements, no previous InSAR study has been conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Há vários métodos que permitem detectar e monitorar subsidências em uma determinada localidade, como, por exemplo, o uso de inclinômetros (MEDHAT; YAMAMOTO;ICHIHASHI, 2023;LI et al, 2014), monitoramento geofísico (ZHOU et al, 2022;GUO et al, 2020) e monitoramento com observações da constelação do Global Navigation Satellite System (GNSS). Este último, contudo, é amplamente utilizado para monitorar pequenas variações no nível do solo, pois pode ser realizado periodicamente, conforme indicado nos estudos de Amagua et al (2022), Vazquez-Ontiveros et al (2022), Mantovani et al (2022), Zhao et al (2020), Wang et al (2020), Andreas et al (2019) e Choudhury et al (2018).…”
Section: Introductionunclassified
“…Há vários métodos que permitem detectar e monitorar subsidências em uma determinada localidade, como, por exemplo, o uso de inclinômetros (MEDHAT; YAMAMOTO;ICHIHASHI, 2023;LI et al, 2014), monitoramento geofísico (ZHOU et al, 2022;GUO et al, 2020) e monitoramento com observações da constelação do Global Navigation Satellite System (GNSS). Este último, contudo, é amplamente utilizado para monitorar pequenas variações no nível do solo, pois pode ser realizado periodicamente, conforme indicado nos estudos de Amagua et al (2022), Vazquez-Ontiveros et al (2022), Mantovani et al (2022), Zhao et al (2020), Wang et al (2020), Andreas et al (2019) e Choudhury et al (2018).…”
Section: Introductionunclassified
“…As some studies have shown, combining different methods for complex landslide monitoring is advantageous. In [11], a combination of multitemporal InSAR and inclinometric boreholes, and in [3], a combination of inclinometers, GNSS receivers, multitemporal InSAR, and UAV photogrammetry were used. The determination of spatial changes in landslide areas using classical geodetic or remote sensing methods was addressed in [12].…”
Section: Introductionmentioning
confidence: 99%